Review of Economic Freedom Impact on FDI: New Evidence from Fragile and Conflict Countries - Moussa, Mohamed; Caha, Havva; Karagoz, Murat (ELSEVIER SCIENCE BV, 2016)
The present thesis aims at investigating the macroeconomic impact of economic freedom on foreign direct investments inflows in both global and regional panel analysis concerning 156 countries through the periods of 1995-2013. Unlike existing literature, it includes often neglected nations such as Fragile and Conflict-Affected states, Sub-Saharan, Oceania, and Post-Soviet countries. This present study investigates not only the global impact of economic freedom on FDI inflows but also makes regional analysis. The paper finds a positive impact of economic freedom on FDI under fixed-effects model in global case where a unit change in economic freedom scales FDI inflows up to 0.0835 units. More specifically, all 9 regions also refer to positive and significant impact of economic freedom on FDI. The highest impact is recorded in European countries, whereas the lowest ones are documented in Oceania and Fragile-Conflict affected states. (C) 2016 The Authors. Published by Elsevier B.V.
Keywords: Economic Freedom; Openness of Economy; Foreign Direct Investments; Neglected Regions; Panel Data Analysis; FOREIGN DIRECT-INVESTMENT; Business & Economics